2023
DOI: 10.1108/jbim-12-2021-0591
|View full text |Cite
|
Sign up to set email alerts
|

CSR orientation for competitive advantage in business-to-business markets of emerging economies: the mediating role of trust and corporate reputation

Abstract: Purpose This study aims to examine the link between corporate social responsibility orientation (CSRO) and competitive advantage (CA) in the context of emerging economies. More specifically, the mediating role of intangible resources, namely, trust and corporate reputation (CR), is investigated to explain the above linkage. Design/methodology/approach This study considered a sample of 326 Saudi Arabian businesses that have extensive business-to-business operations across international markets. The analysis u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 158 publications
1
6
0
Order By: Relevance
“…Third, PLS-SEM is more suitable for relatively small sample sizes (Sarstedt et al , 2019) and has, thus, been applied in recent industrial marketing studies with similar sample sizes (e.g. Hossain et al , 2020; Husain et al , 2022; Zhou et al , 2022; Salam and Jahed, 2023). Therefore, we used the PLS-SEM approach with SmartPLS 3.3.3 for testing the model and report Barron and Kenney approach as a robustness test (see Appendix).…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Third, PLS-SEM is more suitable for relatively small sample sizes (Sarstedt et al , 2019) and has, thus, been applied in recent industrial marketing studies with similar sample sizes (e.g. Hossain et al , 2020; Husain et al , 2022; Zhou et al , 2022; Salam and Jahed, 2023). Therefore, we used the PLS-SEM approach with SmartPLS 3.3.3 for testing the model and report Barron and Kenney approach as a robustness test (see Appendix).…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Although there existed a correlation between CSR and CCA, the exact nature of the correlation was unknown (Mackey et al, 2007; McWilliams & Siegel, 2001; Porter & Kramer, 2006). While the majority of research supported the idea that CSR and CCA were positively correlated (El-Garaihy et al, 2014; Melo & Galan, 2011; Rasheed & Ahmad, 2022; Salam & Jahed, 2023; Vilanova et al, 2009), some studies found the opposite correlation between the two factors (Cordeiro & Sarkis, 1997) and some confirmed a neutral relationship (Wagner, 2005). Orlitzky et al (2003) proposed the idea that CSR was mutually reinforcing under some conditions.…”
Section: Theoretical Foundation and Hypotheses Developmentmentioning
confidence: 99%
“…Businesses are striving for market position and domination in an unstable environment, resultantly, the strategic advantage in practicing CSR is the foundation upon which this degree of success is constructed. Over decades, scholars have strived to explore factors that foster CCA and found that corporate social 1 International University, Ho Chi Minh City, Vietnam 2 Vietnam National University, Ho Chi Minh City, Vietnam 3 Thu Dau Mot University, Binh Duong, Vietnam responsibility (CSR) acts as one of its most crucial drivers (Rasheed & Ahmad, 2022;Salam & Jahed, 2023). During the global recession, firms are under the pressure to act ethically, environmentally, morally, philanthropically, and economically responsible for the society and the environment where they operate in order to improve their reputation, employee commitment, achieve sustainable long-term development (El-Garaihy et al, 2014;Luo & Bhattacharya, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activities of firms that tend to serve as cues or signals to stakeholders include strategic postures and social responsibility actions (Vander and d'Angelo 2022). Other aspects of the signalling theory include market signals, institutional signals and strategic signals (Zerbini 2017;Constantino et al 2021;Salam and Jahed 2023). Market signals refer to unintentional information sent to stakeholders such as competitors, customers, suppliers, governments, bondholders and communities (Herbig 1996).…”
Section: Signalling Theorymentioning
confidence: 99%